แกซิฟิเคชันของไม้ยูคาลิปตัสบนตัวเร่งปฏิกิริยานิกเกิล/โดโลไมต์ - อนวรรตน์ เกตุคง (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
To characterize the influence of operating parameters. These are steam/biomass ratio, temperature of the reactor, composition of catalysts, weight of catalysts, on the catalytic gasification of a eucalyptus biomass into CO and H[subscript 2] in presence of steam. Steam gasification studies were carried out in an atmospheric fixed bed. The gasifier was operated over a temperature in the range of 500-800 ํC whilst, varying a catalyst composition from 0-10% of nickel loading on dolomite in steam flow rate of 0.01-0.07 g/min/g of biomass and 0-1.5g of nickel/dolomite weight. The results obtained showed that the optimum condition is at temperature 700 ํC, percentage of nickel loading on dolomite 9.32% and a steam flow rate of 0.01 g/min/g of biomass. At this condition, comparing the gasification with and without catalyst, it was found that the percentage of hydrogen increased from 41.23% to 45.26% and carbon monoxide increase from 42.75% to 56.45%. In addition, the proportion of hydrogen and carbon monoxide is0.58.